EDITORIAL - -, - (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
We started publishing eJIR in 2016. Entering the third year, we proudly present to you the new Vol. 3.1 of 2018. This first edition of the year 2018 contains a dozen or more research and academic papers covering various interdisciplinary domains. Read more..